Website-Based Digital Training To Develop Market Access For Agricultural Products In Setiris Village, Maro Sebo District, Muaro Jambi Regency. - Ulma, Riri Oktari; Fitri, Yanuar; Nurchaini, Dewi Sri; Elwamendri, Elwamendri; Yulismi, Yulismi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Economic growth refers to an increase in economic activity that increases the production of goods and services. This is a continuous process that indicates the economic performance of a region. Setiris Village in Maro Sebo District, Muaro Jambi Regency, has great potential in the agricultural sector, especially rice, palm oil, rubber and coconut, but faces barriers to market access. This research uses quantitative and qualitative methods to evaluate the impact of website-based digital training in expanding market access for agricultural products in Setiris Village. Implementation stages include preparation and outreach, training on website creation and management, as well as implementation and monitoring. The results show that digital training increases farmers' understanding and skills in digital marketing, expands market reach, and increases sales of agricultural products. Digital technology-based agricultural extension in the Society 5.0 era not only increases production but also environmental sustainability and the quality of life of farmers. Support from village officials and active community participation are the keys to the success of this program.